Responses to a Pennisetum purpureum (Napier grass) basal diet harvested at two different heights and fed with three levels of Leucaena forage to crossbred dairy cows in the subhumid tropics - Muinga, R.W.; Thorpe, W.R.; Topps, J.H.; Mureithi, J.G. (International Livestock Centre for Africa, 1992)
Smallholder dairy production based on zero-grazed Napier grass (Pennisetum purpureum CV Bana) fed to crossbred Bos taurus X Bos indicus cows has been introduced to tropical sub-humid East Africa. Leucaena leucocephala forage offers a cheap convenient source of supplementry protein. Thirty-six Ayrshire/Brown Swiss X Sahiwal cows with one to four previous lactations and which calved during the period 26 March to 2 August 1990 were stall-fed individually to evaluate the effects of harvesting height of Napier grass (1.0 or 1.5m) and level of Leucaena supplement (0.4 or 8kg fresh weight) on dry-matter (DM) intake of Napier grass, total DM intake, liveweight change and milk yield. The study began on day 15 of lactation and lasted 98 days. Average daily milk yield and liveweight during the second week of lactation were covariates for milk yield, and for DM intake and liveweight change, respectively. Harvesting height of Napier grass significantly (P<0.001) affected Napier fodder and total DM intakes, liveweight losses and average daily milk yield. Supplementation with Leucaena tended to increase Napier fodder intake, significantly (P<001) milk yield. The results indicate the importance of stage of harvesting & napier fodder and the benefits from Leucaena supplementation in attaining an acceptable level of performance from crossbred dairy cows in the subhumid tropics.